Susceptibility trends of swine respiratory pathogens from 2019 to 2022 to antimicrobials commonly used in Spain - Anna Vilaró; Elena Novell; Vicens Enrique-Tarancon; Jordi Baliellas; Lorenzo Fraile (Porcine Health Management, 2023)
Abstract Background Antimicrobial resistance is one of the most important health challenges in humans and animals. Antibiotic susceptibility determination is used to select the most suitable drug to treat animals according to its success probability following the European legislation in force for these drugs. We have studied the antibiotic susceptibility pattern (ASP) of Actinobacillus pleuropneumoniae (APP) and Pasteurella multocida (PM) isolates, collected during the period 2019–2022 in Spain. ASP was measured by determining minimum inhibitory concentration using standardized laboratory methods and its temporal trend was determined by logistic regression analysis of non-susceptible/susceptible isolates using clinical breakpoints. Results It was not observed any significant temporal trends for susceptibility of Actinobacillus pleuropneumoniae to ceftiofur, florfenicol, sulfamethoxazole/trimethoprim, tulathromycin and tildipirosin during the study period (p > 0.05). Contrarily, a significant temporal trend (p < 0.05) was observed for quinolones (enrofloxacin and marbofloxacin), tetracyclines (doxycycline and oxyteracycline), amoxicillin, tiamulin and tilmicosin. On the other hand, it was not observed any significant temporal trends for susceptibility of Pasteurella multocida to quinolones (enrofloxacin and marbofloxacin), amoxicillin, ceftiofur, florfenicol and macrolides (tildipirosin, tulathromycin and tilmicosin) during the study period (p > 0.05). Contrarily, a significant temporal trend (p < 0.05) was observed for tetracyclines (oxyteracycline), tiamulin and sulfamethoxazole/trimethoprim. Conclusions In general terms, pig pathogens (APP and PM) involved in respiratory diseases analysed herein appeared to remain susceptible or tended to increase susceptibility to antimicrobials over the study period (2019–2022), but our data clearly showed a different pattern in the evolution of antimicrobial susceptibility for each combination of drug and microorganism. Our results highlight that the evolution of antimicrobial susceptibility must be studied in a case-by-case situation where generalization for drug families and bacteria is not possible even for bacteria located in the same ecological niche.